2000
DOI: 10.1016/s0022-2275(20)32072-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain fatty acid-induced changes in gene expression in neonatal cardiac myocytes

Abstract: Long-chain fatty acids are the most important substrates for the heart. In addition, they have been shown to affect signalling pathways and gene expression. To explore the effects of long-chain fatty acids on cardiac gene expression, neonatal rat ventricular myocytes were cultured for 48 h with either glucose (10 m M ), fatty acids (palmitic and oleic acid, 0.25 m M each), or a combination of both as exogenous substrates. Exposure to fatty acids (both in the absence or presence of glucose) neither affected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 148 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…This speculation is supported by previous in vitro observations. We found that the mere addition of fatty acids to the culture medium of neonatal cardiomyocytes leads to a selective and coordinate induction of the expression of proteins involved in fatty acid uptake and metabolism, thereby showing that fatty acids themselves are able to modulate gene expression in cardiac myocytes (7).…”
Section: Fatty Acidsmentioning
confidence: 85%
See 3 more Smart Citations
“…This speculation is supported by previous in vitro observations. We found that the mere addition of fatty acids to the culture medium of neonatal cardiomyocytes leads to a selective and coordinate induction of the expression of proteins involved in fatty acid uptake and metabolism, thereby showing that fatty acids themselves are able to modulate gene expression in cardiac myocytes (7).…”
Section: Fatty Acidsmentioning
confidence: 85%
“…Ten g of total RNA was size-fractionated on a denaturing gel, transferred to a nylon membrane (Hybond-NX, Amersham, Slough, UK), and fixed with standard techniques. Following prehybridization, the filters were probed with fragments of cDNA of GLUT4, hexokinase II (HKII), FAT/CD36, H-FABP, acyl-CoA synthetase (ACS), longchain acyl-CoA dehydrogenase (LCAD), or uncoupling protein-2 (UCP-2), as described previously (7,12). A 2.1 kb EcoRI fragment of rat glucose transporter GLUT1 cDNA (a gift of Dr. A. Zorzano, University of Barcelona, Spain), a 0.6 kb BglII fragment of rat hexokinase I (HKI; a gift of Dr. J. E. Wilson, Michigan State University, USA), a 0.5 kb KpnI-BamHI fragment of muscletype carnitine palmitoyl transferase 1 (mCPT1; kindly provided by Dr. F. van de Leij, University of Groningen, The Netherlands), a PstI fragment of mouse peroxisome proliferator-activated receptor ␣ (PPAR ␣ ; kindly provided by Dr. J. Auwerx, Institute Pasteur, Lille, France), and a 1.5 kb BamHI fragment of rat PPAR ␤ / ␦ (a gift of Dr. P. A. Grimaldi, University of Nice, France) were also used for hybridization, as well as a 1.0 kb fragment of rat CS generated via reverse transcriptase PCR using for ward (5 Ј -ATCCGTTTCCGAGGCTWY AGT-3 Ј ) and reversed (5 Ј -CGTGAY ACCCCRAACAGGACY-3 Ј ) primers, and a 0.7 kb fragment of rat UCP-3 also generated via RT-PCR using (5 Ј -GGCCATCCTCCG GAA CCATGG-3 Ј ) and (5 Ј -GCGGCCTGCTTGCCTTGTTCA-3 Ј ) as forward and reversed primers, respectively.…”
Section: Northern Blotting Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In these two cases, the final concentration of FA in the medium was 160 and 40 times lower, respectively, than the concentrations used in the present study. In some other cases, neonatal cardiomyocytes have been cultured in the presence of FA-BSA complexes at concentrations similar to that used in the present study, but hypertrophy responses were not the primary focus of these particular studies (23)(24)(25). Nonetheless, chronic palmitate:oleate-BSA has been shown to induce many phenotypic changes in cardiomyocytes, including an increase in the rate of FA oxidation, an increase in the mRNA concentration of several genes involved in FA metabolism, and a decrease in the mRNA concentration of several genes involved in glucose metabolism (23).…”
Section: Discussionmentioning
confidence: 99%